"100% They Are Destroying Our Beautiful Town": toxic Conversations About Homelessness on Public Facebook Community Groups - Robillard, Abigail (European journal on criminal policy and research, 2023)
In this paper, we use a qualitative content analysis to understand how homelessness is discussed in 14 public Facebook groups from three Canadian mid-sized cities. We find that stigma about homelessness is created and perpetuated among these groups in particular ways. First, the language used "others" those experiencing homelessness and perpetuates the idea that "they are not from here." We demonstrate that individuals experiencing homelessness are shamed and exposed during life-sustaining activities through images and videos that are posted. The paradox of unhoused people attempting to live private lives in public spaces is exacerbated by social media, and we demonstrate the repercussions including calls for vigilante justice and violence against those experiencing homelessness. Finally, we provide suggestions to counter the toxic communication on social media and encourage social media campaigns which target stereotypical assumptions of homelessness, which may increase public support and advocacy for structural responses.